Computer simulations and suitability of open nucleus breeding schemes for dairy cattle under Philippine conditions - Bondoc, Orville L. (1997)
Computer simulations using deterministic models were performed to evaluate the genetic properties of the open nucleus breeding system for smallholder dairy cattle.
Higher asymptotic (steady-state) selection response but longer genetic (improvement) lag and improved mean breeding values in the nucleus, base, and in the total breeding population are predicted when the fraction of nucleus dams born in the base is increased. The same parameters seem to be slightly affected by the proportion of the total breeding population included in the nucleus.

When some field problems and farm inadequacies under Philippine conditions are considered, genetic responses are reduced especially when fewer facilities to record female performance in the nucleus are used, when age at first calving is prolonged, when heritability (and repeatability) values in the base are lower than in the nucleus, when females in the base herds are not recorded, and when there is a low correlation in economic merit between the nucleus and the base test environment.

The results of the computer simulations indicate that genetic improvement of dairy cattle in smallholder farms in the Philippines can be attained with the establishment of an open nucleus breeding system. Parallel programs can be suggested for the local improvement of beef cattle and water buffaloes.
Keywords: Dairy cattle; Cattle breeding; Computer simulation